1961
DOI: 10.1111/j.1476-5381.1961.tb01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Amine Levels and Sympathetic Blockade After Guanethidine and Bretylium

Abstract: A single dose of guanethidine produces a substantial, long-lasting depletion of tissue catecholamines in the rat, whereas a similar dose of bretylium has no effect. Both drugs produce block of the eserine-induced sympathetic pressor effect. Block by guanethidine is induced more rapidly than is amine depletion. When amine depletion is maximal, a noradrenaline infusion is capable of restoring the response to eserine, but no restoration of the response to eserine occurs after noradrenaline infusion into bretylium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
3

Year Published

1963
1963
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 16 publications
11
63
3
Order By: Relevance
“…As the pressor effects of such small doses of dimethylphenylpiperazinium are mainly mediated through a release of amines from the adrenal medulla, the above finding suggests that discharge of the adrenal medullary hormone(s) plays no part in the pressor response to physostigmine, a conclusion drawn by Legid & Varagi6 (1961) and by Cass & Spriggs (1961), who demonstrated that the pressor effect of physostigmine was unaltered by adrenalectomy.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As the pressor effects of such small doses of dimethylphenylpiperazinium are mainly mediated through a release of amines from the adrenal medulla, the above finding suggests that discharge of the adrenal medullary hormone(s) plays no part in the pressor response to physostigmine, a conclusion drawn by Legid & Varagi6 (1961) and by Cass & Spriggs (1961), who demonstrated that the pressor effect of physostigmine was unaltered by adrenalectomy.…”
Section: Discussionsupporting
confidence: 57%
“…Reduction or abolition of the response by antiadrenaline agents, by large doses of hexamethonium and by bretylium or guanethidine suggests that the central stimulant effect of physostigmine may be mediated by way of the established peripheral sympathetic pathways. The pressor response to physostigmine in the rat is thus in many ways similar to the effects of sympathetic nerve stimulation and has been used by Cass & Spriggs (1961) to assess sympathetic function.…”
mentioning
confidence: 99%
“…Boura, Copp, Duncombe, Green & McCoubrey (1960) suggested that bretylium specifically anaesthetizes sympathetic postganglionic fibres. Cass & Spriggs (1961) reported that guanethidine inhibited the effect of sympathetic nerve stimulation. They suggested that the primary action of guanethidine is to produce a bretylium-like adrenergic block.…”
Section: The Effects Ofpremedication and Anaesthesiamentioning
confidence: 99%
“…This is not so for guanethidine, which produces sympathetic blockade before extensive depletion of tissue noradrenaline has occurred (Cass & Spriggs, 1961;Gaffney, Chidsey & Braunwald, 1963). Guanethidine acts like bretylium in preventing the release of noradrenaline from the cat spleen into the circulation when the splenic nerves are stimulated (Hertting et al, 1962).…”
Section: Discussionmentioning
confidence: 99%